Pengaruh harga, Kualitas Layanan, Citra Destinasi terhadap Loyalitas Wisatawan Kawah Wurung Bondowoso Melalui Kepuasan Berkunjung Sebagai Variabel Intervening - Auliyah Ilzana Hakiki; Ahmad Sauqi; Muhdar Muhdar (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the direct and indirect effects of Price (X1), Service Quality (X2), and Destination Image (X3) on Tourist Loyalty (Y) at Kawah Wurung, Bondowoso, mediated by Visit Satisfaction (Z). A quantitative approach using the Partial Least Squares (PLS) method was employed. The study population consisted of tourists who had visited Kawah Wurung, Bondowoso, with a sample of 95 respondents obtained through questionnaires. Data analysis was conducted using SmartPLS 4 software. The results indicate that Price and Destination Image have a significant effect on Satisfaction but not on Loyalty; Service Quality significantly affects both; and Visit Satisfaction has a strong impact on Loyalty. Indirectly, Price and Destination Image significantly influence Loyalty through Visit Satisfaction, whereas Service Quality does not. The study concludes that Visit Satisfaction plays a crucial role as a mediating variable; therefore, destination managers should prioritize maintaining reasonable pricing, enhancing service quality, and upholding the positive image of Kawah Wurung, Bondowoso, to boost tourist satisfaction and loyalty.